Developing scales for assessing metaverse characteristics and testing their utility - Chaeeun Boo; Ayoung Suh (Computers in Human Behavior Reports, 2024)
Despite the rapidly growing scholarly and applied interest in the metaverse, inquiries concerning the defining features of the metaverse and the appropriate methodology for assessing these features remain unresolved. In order to address these inquiries, we executed two empirical investigations. In Study 1, we initially conceptualize the attributes of the metaverse and develop scales for assessing the metaverse characteristics. Subsequently, we evaluate the validity and reliability of this metric through the analysis of data acquired from 106 participants utilizing prominent metaverse platforms such as Zepeto, Roblox, and Ifland. In Study 2, we establish a theoretical model by associating metaverse characteristics with experiential value users perceive and appraising the construct's utility to account for an individual's continuance intention. The proposed model was tested through a sample of 218 metaverse users. The findings of Study 1 demonstrate that the metaverse is delineated by five factors: seamlessness, interoperability, concurrence, presence, and creator economy. The results of Study 2 reveal that, despite the creator economy being a legitimate attribute of the metaverse, its impact on a user's experiential value remains insignificant in the current metaverse platforms. This research contributes to the body of knowledge on the metaverse by developing scales and testing their utility. The outcomes are anticipated to yield practical insights for metaverse service providers on strategies for sustaining user engagement by leveraging the inherent attributes of the metaverse.